UPAYA PENINGKATAN KESEHATAN LANJUT USIA MELALUI PROGRAM PELATIHAN SENAM LANSIA BUGAR - Faridah Faridah (Jurnal Abdimas Kesehatan (JAK), 2019)
Elderly Health Efforts are basic and comprehensive plenary health efforts in the field of elderly health which which promotive, preventive, curatf and rehabilitative so that the elderly can stay healthy. The sports activities at PSTW Budi Luhur Jambi carry out activities held once a week, but the physical condition of the elderly increasingly decreases, it is necessary to do an activity that will move the elderly to have a healthier life, through gymnastics programs for ages.The method of implementation is carried out by examining breathing and pulse before and after carrying out activities by recording their identity (name, age, gender). This activity was held on November 16, 2016, the location of the activity was held in Jambi Paradise tourist site. The results of this activity are respiratory and pulse examinations before and after performing a 15-minute leisurely activity. 10 people (30.3%) had normal breathing, while 9 pulse (30%) had a normal pulse. Examination of breathing and pulse after doing activity obtained results of respiratory calculations as many as 4 people (13.3%) had normal breathing, while the pulse examination as many as 5 people (17%) had a normal pulse.Decreased physical ability of the elderly due to deterioration in the function of the heart and lungs, it is better that physical activity be adjusted to the conditions and physical abilities of the elderly.